Prevalence of diabetic retinopathy, cataract and visual impairment in patients with diabetes in sub-Saharan Africa. Issue 2 (21st April 2011) - Glover, Simon J; Burgess, Philip I; Cohen, Danielle B; Harding, Simon P; Hofland, Helma W C; Zijlstra, Eduard E; Allain, Theresa J
Abstract : Background/aims: There are few published data on the prevalence of diabetic retinopathy in sub-Saharan Africa. We report the prevalence of all grades of retinopathy and associations with systemic parameters in patients attending a secondary care diabetes clinic in Blantyre, Malawi. Methods: Cross-sectional study of all patients attending for diabetes care in a hospital setting. Clinical examination and biochemical testing was performed to assess visual acuity (VA), grade of retinopathy (slit lamp biomicroscopy), microvascular complications, glycaemic control, hypertension and HIV status. Sight-threatening diabetic retinopathy (STDR) was defined as moderate preproliferative retinopathy or worse, circinate maculopathy or exudates within one disc diameter of the foveal centre or clinically significant macular oedema. Results: In patients with type 2 diabetes (n=249) the prevalence (95% CI) of any retinopathy, STDR and proliferative diabetic retinopathy (PDR) was 32.5% (26.7 to 38.3%), 19.7% (14.7 to 24.6%) and 4.8% (2.2 to 7.5%), respectively. The presence of STDR was associated with albuminuria (OR 2.6; p=0.02), the presence of neuropathy (OR 3.4; p=0.005) and insulin use (OR 5.3; p=0.0004), but not with HIV status. In patients with type 1 diabetes (n= 32), the prevalence of any retinopathy, STDR and PDR was 28.1% (12.5 to 43.7%), 18.8% (5.2 to 32.2%) and 12.5% (1.0 to 24.0%), respectively. 12.1% of study subjects had VA worse than 6/18 (20/60). Conclusion: This study provides baseline information on prevalence of all grades of retinopathy and STDR in consecutive cases attending an urban/semi-urban diabetes clinic in sub-Saharan Africa. Prevalence of STDR was high and in type 2 diabetes was associated with albuminuria, neuropathy and insulin use.